Investment Behavior of Secondary Equity Investors : An Examination of the Relationship Among the Biases - Renu Isidore, R.; Christie, P. (Indian Journal of Finance, 2018)
Behavioral finance attempts to explain the emotions in the stock market which lead to anomalous stock market behavior. Behavioral biases exhibited by the investors explain their irrational decision making. Knowledge about the interaction among the biases would help to comprehend the investors’ financial personality better. Using a dataset of 436 secondary equity investors residing in Chennai, this study measured eight behavioral biases on a Likert scale through a questionnaire survey. The biases studied included mental accounting, anchoring, gambler’s fallacy, availability, loss aversion, regret aversion, representativeness, and overconfidence. Significant relationships among the behavioral biases were documented in the study. The biases: (a) overconfidence, regret aversion, and anchoring biases; (b) loss aversion and anchoring; (c) representativeness, gambler’s fallacy, and mental accounting; (d) mental accounting and availability biases exhibited by the secondary equity investors were found to be interrelated. Hence, the financial advisors could improve their advice and recommend guidelines to the investors based on the biases they are likely to exhibit.